Adoption of corporate governance practices by startups in the northeast - Teixeira, Thalya Teles; Gatsios, Rafael Confetti (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: This study analyzed the adoption of corporate governance practices by Startups in the Northeast of Brazil, their difficulties in implementing governance, perceptions about the subject and possible impacts on attracting investment. Methodology: To this end, a qualitative study was carried out using interviews with founders and directors of Startups. The results were compared with other studies, existing literature and research into the Startup ecosystem. Results: It was found that some of the practices are adopted with varying degrees of formality, but with difficulties due to the companies' need to prioritize scaling their operations and increasing sales. In addition, it was noted that the adoption of governance practices can have an impact on raising investment. As a result, although governance practices don't have such a direct impact on the development of these Startups, they can help them to become better organized and structured. Contributions of the Study: This study fills an existing gap in research on governance practices adopted by Startups in the Northeast, contributing to an understanding of the most adopted practices and their impact on attracting funding. The results can provide a basis for future research, guide Startups interested in GC and support ecosystem agents and investors in their decision-making.